التاريخ الإسلاميّ مصدرًا للإبداع المسرحيّ Islamic History as a Source of Play Writing - Ahmad, Muhammad Anwar; Bahjat, Munjid Mustafa (Akademik Pengajian Islam Universiti Malaya, 2019)
التاريخ الإسلاميّ مصدرًا للإبداع المسرحيّ Islamic History ; Source of Play Writing